Kegiatan Pelatihan Implementasi Schoology dalam KBM untuk Meningkatkan Keahlian dan Etika Siswa SMA Menggunakan ICT - Anita Anggraeni; Cynantia Rachmijati (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2021)
The quality of learning in general at SMK PGRI 2 Cimahi based on the results of discussions with the English teacher is that in general they have enough enthusiasm to learn English, but learning is still fixated on learning resource media in the form of worksheets. Thus they are more focused on the results of working on worksheets. The development of information and communication technology has brought enormous changes to the advancement of the world of education. The form of the development of information technology applied in the world of education is E-Learning. One of the platforms that can be used as an interactive learning medium is Schoology. The use of Schoology media requires students to always be connected to the internet network. Positive supervision from teachers and parents is expected so that students do not access things that are negative in nature. Therefore, the community service activity entitled "Schoology Implementation Training Activities in Teaching and Learning to improve the skills and ethics of high school students using ICT" is to provide socialization related to the use of Schoology for teachers as well as socializing ethics on the internet for students. This activity was carried out on January 22-24, 2021 which was carried out online because of the Covid-19 PSBB. One of the indicators that can be measured is that seen from this activity, teachers and students can use Schoology applications well and students can communicate according to the principle of netiquette (internet etiquette). Therefore we declared that this community service activity was deemed as successful.